Light-emitting element and method for manufacturing light-emitting element

By using a combined structure of Ru, Rh alloy and DBR layer on the p-side electrode of the Group III nitride semiconductor light emitting element, the problem of insufficient ohmic contact and reflectivity in the ultraviolet region in the prior art is solved, and efficient light extraction and stable contact resistance are achieved.

CN119677257APending Publication Date: 2025-03-21TOYODA GOSEI CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411127986.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-15
Filing Date
2024-08-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, the Group III nitride semiconductor light emitting element has shortcomings in the ohmic contact and reflectivity of the ultraviolet region, especially the light reflectivity in the UVC wavelength range is low, and the contact resistance of the p-side electrode is prone to deterioration.

Method used

A p-side electrode composed of Ru, Rh or an alloy thereof is used, and an insulating DBR layer is provided thereon, and ultraviolet light is reflected through the DBR layer to improve the light extraction efficiency, while maintaining the thinness of the p-side electrode to avoid deterioration of contact resistance.

Benefits of technology

The formation of an efficient ohmic contact between the p-type layer and the p-side electrode in the ultraviolet region is achieved, and the reflectivity of the ultraviolet ray is improved, the light extraction efficiency is enhanced, and the deterioration of the contact resistance is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677257A_ABST
    Figure CN119677257A_ABST
Patent Text Reader

Abstract

Provided are a light-emitting element capable of ohmic contact with a p-side electrode and capable of improving ultraviolet reflectance, and a method for manufacturing the light-emitting element. The flip-chip ultraviolet-emitting light-emitting element is provided with: an n-type layer comprising an n-type group III nitride semiconductor; an active layer provided on the n-type layer and comprising a group III nitride semiconductor; a p-type layer provided on the active layer and comprising a p-type group III nitride semiconductor; a p-side electrode which is provided on the p-type layer, comprises a layer that is in contact with the p-type layer and is composed of Ru, Rh or an alloy having Ru and Rh as main components, and has a thickness that allows ultraviolet light having an emission wavelength to pass therethrough; an insulating DBR layer that is in contact with a portion of the p-side electrode, is provided on the portion of the p-side electrode, and reflects ultraviolet light having an emission wavelength; and a second p-side electrode electrically connected to the p-side electrode via a hole formed in a region above the p-side electrode in the DBR layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a light emitting element and a method for manufacturing the light emitting element. Background Art

[0002] On the one hand, the wavelength of ultraviolet light of solid-state light-emitting elements using group III nitride semiconductors corresponds to a wavelength band in the range of about 210nm to 400nm. On the other hand, it is known that UVC (wavelength 100nm to 280nm) can efficiently sterilize and disinfect, and the use of UVC (wavelength 100nm to 280nm) for sterilization and disinfection of water, air, etc. has attracted attention. Therefore, the demand for group III nitride semiconductor light-emitting elements that radiate ultraviolet light with a wavelength corresponding to UVC has increased, and research and development towards high efficiency are being actively carried out.

[0003] Patent document 1 describes a structure having an Rh layer in contact with a p-type semiconductor layer and having a thickness of less than 10 nm and an Al layer in contact with the Rh layer and having a thickness of more than 20 nm, as a p-side electrode of a light-emitting element composed of a group III nitride semiconductor that emits UVC light. The document also records that by adopting such a structure, the contact resistance can be reduced and the reflectivity can be improved. In addition, the document also records that by annealing the p-electrode, the Rh layer and the Al layer are mixed, and the reflectivity is improved compared to a single Rh layer.

[0004] Patent document 2 describes a structure having a transparent electrode, a p-electrode, and a p-side junction electrode, as a p-side electrode of a light-emitting element composed of a group III nitride semiconductor that emits UVC light. The transparent electrode is in contact with the p-type semiconductor layer and is disposed on the p-type semiconductor layer, and is composed of a transparent conductive material such as ITO or IZO. The p-electrode is in contact with the transparent electrode and is disposed on the transparent electrode, and is composed of Ni / Au or Ni / Al, etc. The p-side junction electrode is in contact with the p-electrode and is disposed on the p-electrode, and is composed of Au, etc.

[0005] Patent document 2 records that a reflective insulating film composed of SiO2, SiN, SiO2 / Al / SiO2, a distributed Bragg reflector (DBR), etc. is also arranged across the transparent electrode and the p-layer to reflect the light radiated from the active layer constituting the semiconductor layer to improve light extraction.

[0006] Patent document 3 describes a structure in which a light-emitting element composed of a Group III nitride semiconductor that emits red, green, and blue light comprises: a conductive layer that is in contact with and disposed on a p-type semiconductor layer and has high transmittance for the emission wavelength, a conductive reflective layer that is in contact with and disposed on the conductive layer, an insulating layer that is in contact with and disposed on the reflective layer, and an electrode portion that is disposed on the insulating layer and has a shape that penetrates the insulating layer.

[0007] The conductive layer uses a transparent oxide-based material with high transmittance for the emission wavelength, such as one or more of ITO, TO, IZO, IZTO, IAZO, IGZO, IGTO, AZO, ATO, GZO, IrOx, RuOx, RuOx / ITO, Ni, Ag, Ni / IrOx / Au, or Ni / IrOx / Au / ITO. The reflective layer includes a reflective metal with high conductivity or an alloy thereof, such as at least one of Ni, Pd, Ru, Mg, Zn, Hf, Ag, Al, Au, Pt, Cu, or Rh. The insulating layer can be formed of at least one of Al2O3, SiO2, Si3N4, TiO2, or AlN, and can include a DBR.

[0008] Patent Document 1: Japanese Patent Application Publication No. 2022-30948

[0009] Patent Document 2: Japanese Patent Application Publication No. 2023-34227

[0010] Patent Document 3: Japanese Patent Application Publication No. 2015-220456

[0011] At present, the materials that can form ohmic contact with p-AlGaN and p-GaN have low reflectivity with respect to light in the ultraviolet region (especially UVC). Al has high reflectivity for light in the ultraviolet region, but cannot form ohmic contact with p-AlGaN and p-GaN. Therefore, it is expected that the p-side electrode can form an ohmic contact and improve the ultraviolet reflectivity.

[0012] In addition, in Patent Document 1, there is a possibility that the p-layer contacts Al due to the diffusion of Al, which may lead to deterioration of the contact resistance. In Patent Document 2, there is room for improvement from the perspective of ohmic contact and reflectivity. Patent Document 3 does not target ultraviolet luminescent elements, so there is room for research in order to improve ohmic contact in the ultraviolet region and improve ultraviolet reflectivity. Summary of the invention

[0013] The present invention has been made in view of the above background, and provides a light emitting element in which a p-side electrode can form an ohmic contact and the ultraviolet reflectivity can be improved, and a method for manufacturing the same.

[0014] One embodiment of the present invention is a flip-chip, ultraviolet-light-emitting light-emitting element, in which the light-emitting element comprises: an n-type layer composed of an n-type Group III nitride semiconductor; an active layer, which is arranged on the above-mentioned n-type layer and composed of a Group III nitride semiconductor; a p-type layer, which is arranged on the above-mentioned active layer and composed of a p-type Group III nitride semiconductor; a p-side electrode, which is arranged on the above-mentioned p-type layer and includes a layer composed of Ru, Rh or an alloy with them as the main component and in contact with the above-mentioned p-type layer, and is set to a thickness that allows ultraviolet light of the emission wavelength to pass through; an insulating DBR layer, which is in contact with a part of the above-mentioned p-side electrode and is arranged on the part of the above-mentioned p-side electrode, and reflects the ultraviolet light of the emission wavelength; and a second p-side electrode, which is electrically connected to the above-mentioned p-side electrode via a hole formed in the area above the above-mentioned p-side electrode in the above-mentioned DBR layer.

[0015] Another aspect of the present invention is a method for manufacturing a flip-chip ultraviolet luminescent light-emitting element, wherein the method comprises: an n-type layer forming step, in which an n-type layer composed of an n-type group III nitride semiconductor is formed; an active layer forming step, in which an active layer composed of a group III nitride semiconductor is formed on the n-type layer; a p-type layer forming step, in which a p-type layer composed of a p-type group III nitride semiconductor is formed on the active layer; and a p-side electrode forming step, in which a p-side electrode is formed between the p-type layer and the active layer. A p-side electrode having a thickness of being formed on the p-type layer and being in contact with the p-type layer and transmitting ultraviolet light of the emission wavelength is formed; a DBR layer forming step, in which an insulating DBR layer for reflecting ultraviolet light of the emission wavelength is formed on the p-side electrode in a manner of being in partial contact with the p-side electrode; and a second p-side electrode forming step, in which a second p-side electrode is formed in a manner of being electrically connected to the p-side electrode via a hole formed in the DBR layer in a region above the p-side electrode.

[0016] According to the above-mentioned method of the present invention, by making the p-side electrode provided in contact with the p-type layer adopt a structure including a layer composed of Ru, Rh or an alloy with them as the main component and making the layer contact with the p-type layer, an ohmic contact between the p-type layer and the p-side electrode can be formed in the ultraviolet region. In addition, by making the DBR layer that reflects ultraviolet light of the emission wavelength and has insulation contact with the p-side electrode and provided on the p-side electrode, the p-side electrode can be formed thinner. By making the p-side electrode thinner, the ultraviolet light emitted by the active layer is not easily absorbed by the p-side electrode, and the ultraviolet light can be transmitted through the p-side electrode to reach the DBR layer. As a result, the ultraviolet light can be efficiently reflected by the DBR layer, and the light extraction efficiency can be improved. In addition, the DBR layer has insulation, so even if the p-side electrode is thinned and the DBR layer is assumed to be partially in contact with the upper surface of the p-type layer, problems such as deterioration of contact resistance will not occur.

[0017] As described above, according to the above aspect, it is possible to provide a light emitting element and a method for manufacturing the light emitting element in which the p-side electrode can be in ohmic contact and the ultraviolet reflectivity can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a diagram showing the structure of the light emitting element according to Embodiment 1 and is a cross-sectional view in a direction perpendicular to the principal surface of the substrate.

[0019] Figure 2 It is a diagram showing the structure of the light-emitting element of Embodiment 1, and is a plan view viewed from the upper surface of the element.

[0020] Figure 3 It is a diagram showing the manufacturing process of the light emitting element of Embodiment 1.

[0021] Figure 4 It is a diagram showing the manufacturing process of the light emitting element of Embodiment 1.

[0022] Figure 5 It is a diagram showing the manufacturing process of the light emitting element of Embodiment 1.

[0023] Figure 6 It is a diagram showing the manufacturing process of the light emitting element of Embodiment 1.

[0024] Figure 7 It is a diagram showing the manufacturing process of the light emitting element of Embodiment 1.

[0025] Figure 8 It is a diagram showing the manufacturing process of the light emitting element of Embodiment 1.

[0026] Fig. 9 It is a diagram showing the manufacturing process of the light emitting element of Embodiment 1.

[0027] Fig.10 It is a graph showing the wavelength dependence of the reflectivity of DBR and Al.

[0028] Description of Reference Numerals

[0029] 10...substrate; 11...n-type layer; 12...active layer; 13...electron blocking layer; 14...composition gradient layer; 15...p-type contact layer; 16...n-side electrode; 17...p-side electrode; 18, 18A, 18B...etching stop layer; 19...DBR layer; 20...protective layer; 21...n-side pad electrode; 22...p-side pad electrode; 23-25...holes. DETAILED DESCRIPTION

[0030] The flip-chip ultraviolet luminescent element comprises: an n-type layer composed of an n-type Group III nitride semiconductor; an active layer, which is arranged on the above-mentioned n-type layer and composed of a Group III nitride semiconductor; a p-type layer, which is arranged on the above-mentioned active layer and composed of a p-type Group III nitride semiconductor; a p-side electrode, which is arranged on the above-mentioned p-type layer and includes a layer composed of Ru, Rh or an alloy with them as the main component and in contact with the above-mentioned p-type layer, and is set to a thickness that allows ultraviolet light of the emission wavelength to pass through; an insulating DBR layer, which is in contact with a part of the above-mentioned p-side electrode and is arranged on a part of the above-mentioned p-side electrode, and reflects ultraviolet light of the emission wavelength; and a second p-side electrode, which is electrically connected to the above-mentioned p-side electrode via a hole formed in the area above the above-mentioned p-side electrode in the above-mentioned DBR layer.

[0031] Alternatively, in the light-emitting element, the DBR layer is in contact with a portion of the p-side electrode and is disposed on a portion of the p-side electrode, and is disposed in contact with the side of at least one of the n-type layer, the active layer, and the p-type layer. The DBR layer has insulating properties, and therefore, can be disposed not only in contact with the p-side electrode and disposed on the p-side electrode, but also in contact with the side of at least one of the n-type layer, the active layer, and the p-type layer. As a result, the area capable of reflecting ultraviolet light can be expanded, and the light extraction efficiency can be improved. Here, the side surfaces of each layer constituting the semiconductor layer (n-type layer, active layer, p-type layer) include at least a portion of the outer peripheral surface of the semiconductor layer, the inner peripheral surface of the hole when a hole or a groove is formed, or the side surface of the groove.

[0032] In addition, the wavelength of the ultraviolet luminescent element may be greater than 200 nm and less than 280 nm. Within the range of the luminescent wavelength, when the DBR layer is used as the reflective layer, the reflectivity can be more effectively improved compared to the case where Al is used as the reflective layer. Therefore, the light extraction efficiency can be improved.

[0033] In addition, the DBR layer may include HfO 2 . Thus, in particular, a high reflectivity can be obtained within a range where the emission wavelength is between 200 nm and 280 nm. In addition, the DBR layer may include components other than HfO 2 .

[0034] In addition, the thickness of the p-side electrode may be greater than 1 nm and less than 50 nm. By making the p-side electrode greater than 1 nm and less than 50 nm, the reflectivity of ultraviolet rays can be improved. Furthermore, when the thickness of the p-side electrode is made greater than 1 nm and less than 50 nm, even if the DBR layer partially contacts the upper surface of the p-type layer, since the DBR layer has insulating properties, problems such as deterioration of contact resistance will not occur.

[0035] Furthermore, the p-type layer may include a p-type contact layer which is in contact with the p-side electrode and is made of GaN, and the thickness of the p-type contact layer may be greater than or equal to 1 nm and less than or equal to 50 nm.

[0036] Furthermore, the p-type layer may include a p-type contact layer which is in contact with the p-side electrode and is made of AlGaN having an Al composition of 50 mol % or less, and the thickness of the p-type contact layer may be 20 nm or less.

[0037] In addition, the manufacturing method of the above-mentioned light-emitting element can be as follows. That is, the manufacturing method of the flip-chip and ultraviolet light-emitting light-emitting element comprises: an n-type layer forming step, in which an n-type layer composed of an n-type group III nitride semiconductor is formed; an active layer forming step, in which an active layer composed of a group III nitride semiconductor is formed on the above-mentioned n-type layer; a p-type layer forming step, in which a p-type layer composed of a p-type group III nitride semiconductor is formed on the above-mentioned active layer; a p-side electrode forming step, in which a layer composed of Ru, R and N is formed on the above-mentioned p-type layer. h or an alloy with them as main components and in contact with the above-mentioned p-type layer and having a p-side electrode of a thickness that allows ultraviolet light of the emission wavelength to pass through; a DBR layer forming step, in which a DBR layer with insulation that reflects ultraviolet light of the emission wavelength is formed on the above-mentioned p-side electrode in a manner that is in partial contact with the above-mentioned p-side electrode; and a second p-side electrode forming step, in which a second p-side electrode is formed in a manner that is electrically connected to the above-mentioned p-side electrode via a hole formed in the area above the above-mentioned p-side electrode in the above-mentioned DBR layer.

[0038] (Implementation Method 1)

[0039] Figure 1 1 is a diagram showing the structure of the light emitting element 1 according to Embodiment 1, and is a cross-sectional view in a direction perpendicular to the main surface of the substrate. Figure 2This is a diagram showing a planar pattern of the light emitting element 1 according to Embodiment 1. Figure 1 The cross section and Figure 2 The cross section at AA corresponds to .

[0040] like Figure 1 As shown, the light emitting element 1 of Embodiment 1 comprises a substrate 10, an n-type layer 11, an active layer 12, an electron blocking layer 13, a composition graded layer 14, a p-type contact layer 15, an n-side electrode 16, a p-side electrode 17, an etching stop layer 18, a DBR (dispersive Bragg reflector) layer 19, a protective layer 20, an n-side pad electrode 21, and a p-side pad electrode 22. Hereinafter, the stacked structure from the n-type layer 11 to the p-type contact layer 15 is sometimes referred to as a semiconductor layer.

[0041] The light emitting element 1 of Embodiment 1 is a flip-chip type that extracts light from the back side (the side opposite to the n-type layer 11 side) of the substrate 10. The emission wavelength is a predetermined wavelength in the range of 210 nm to 280 nm, which is in the UVC band (100 nm to 280 nm).

[0042] 1. Structures of light-emitting elements

[0043] The structure of each layer of the light emitting element 1 according to Embodiment 1 will be described in detail.

[0044] The substrate 10 is a substrate made of sapphire with the c-plane as the main plane. The plane orientation of the main plane of the sapphire can also be the a-plane. In addition, it can also have an off-angle of 0.1 to 2 degrees in the m-axis direction. It is also possible that the back side of the substrate 10 (the surface on the opposite side of the n-type layer 11) becomes the main light extraction surface. It is also possible that an anti-reflection film is provided on the back side of the substrate 10 to achieve an improvement in the light extraction rate. In addition, it is also possible to provide bumps and depressions on the surface of the substrate 10 to achieve an improvement in the light extraction rate. In addition, as the substrate 10, an AlN substrate or an AlN template substrate having an AlN layer formed on a sapphire substrate can also be used.

[0045] The thickness of the substrate 10 is, for example, 1000 μm or less, and preferably 400 μm or more and 700 μm or less. This can suppress light extraction from the side surfaces of the substrate 10 and improve the on-axis strength.

[0046] Alternatively, the substrate 10 may be removed by a method such as LLO (laser lift-off). Alternatively, an antireflection film may be provided on the back surface of the substrate 10 to improve light extraction efficiency.

[0047] The n-type layer 11 is located on the substrate 10. The n-type layer 11 is composed of n-AlGaN. The Al composition (the molar ratio of Al in the entire group III metal) is, for example, 60% to 90%. The n-type impurity is Si, and the Si concentration is, for example, 1×10 18 cm-3 ~5×10 19 cm -3 The thickness of the n-type layer 11 is, for example, 0.5 μm to 5 μm. In addition, the C concentration of the n-type layer 11 is 1×10 15 cm -3 ~1×10 19 cm -3 The n-type layer 11 may be composed of a plurality of layers. For example, it may be a superlattice layer in which AlGaN with different Al compositions are alternately stacked. In addition, a base layer composed of AlN may be provided between the substrate 10 and the n-type layer 11. In addition, substances other than Si may be used as n-type impurities.

[0048] The active layer 12 is located on the n-type layer 11. The active layer 12 has an SQW structure in which a barrier layer, a well layer, and a barrier layer are stacked in order from the n-type layer 11. The active layer 12 may have an MQW structure. In this case, the number of repetitions is, for example, 2 to 10.

[0049] The well layer is made of AlGaN, and its Al composition is set according to the desired emission wavelength. The Si concentration of the well layer is, for example, 1×10 18 cm -3 The following may be non-doped. The thickness of the well layer is, for example, 0.5 nm to 5 nm.

[0050] The barrier layer is AlGaN with a higher Al content than the well layer. The Al content is, for example, 50% to 100%. The Si concentration of the barrier layer is, for example, 2×10 19 cm -3 The following may be non-doped. The thickness of the barrier layer is, for example, 3 nm to 30 nm. The barrier layer may also be AlGaInN having a larger band gap energy than the well layer. In addition, the layer in contact with the electron blocking layer 13 in the barrier layer preferably has a thickness of 0.5 nm to 10 nm.

[0051] Alternatively, a hole blocking layer may be provided between the n-type layer 11 and the active layer 12. This can prevent holes injected from the p-side electrode 17 from diffusing to the n-type layer 11 side beyond the active layer 12. The hole blocking layer is AlGaN or AlN having an Al composition higher than that of the barrier layer of the active layer 12. The thickness of the hole blocking layer is, for example, 1 molecular layer to 2 nm. In the case of AlN, 1 molecular layer is approximately 0.26 nm.

[0052] The electron blocking layer 13 is located on the active layer 12. The electron blocking layer 13 has a double-layer structure in which a first electron blocking layer and a second electron blocking layer are stacked in order from the active layer 12 side. The electron blocking layer 13 prevents electrons injected from the n-side electrode 16 from diffusing to the composition gradient layer 14 side beyond the active layer 12.

[0053] In addition, the electron blocking layer 13 does not necessarily need to have a two-layer structure, and may be only the first electron blocking layer.

[0054] The first electron blocking layer is composed of AlGaN or AlN having an Al composition higher than that of the barrier layer of the active layer 12, and the Al composition is, for example, 90% to 100%. In addition, the first electron blocking layer may be doped with a p-type impurity or may be undoped. The p-type impurity is, for example, Mg. In the case of Mg doping, the Mg concentration is, for example, 3×10 20 cm -3 In addition, the thickness of the first electron blocking layer is, for example, 1 nm to 10 nm.

[0055] The second electron blocking layer is composed of AlGaN with a lower Al composition than that of the first electron blocking layer, and the Al composition is, for example, 80 to 99%. By providing the second electron blocking layer, the difference in Al composition with the composition gradient layer 14 is adjusted. If only the AlN of the first electron blocking layer is used, the resistance will increase, and if the first electron blocking layer is made thinner, the electron blocking performance will decrease. Therefore, by providing the second electron blocking layer, both low resistance and electron blocking function can be achieved. In addition, the second electron blocking layer can also be doped with p-type impurities or can be undoped. In the case of Mg doping, the Mg concentration is, for example, 3×10 20 cm -3 In addition, the thickness of the second electron blocking layer is, for example, 1 nm to 10 nm.

[0056] The composition graded layer 14 is located on the electron blocking layer 13. The composition graded layer 14 has a two-layer structure in which a first composition graded layer and a second composition graded layer are sequentially stacked from the electron blocking layer 13 side.

[0057] The composition graded layer 14 is a layer that becomes p-type by a method called polarization doping. That is, the composition graded layer 14 is a layer in which the Al composition changes in the thickness direction, and is set so that the Al composition decreases as it moves away from the electron blocking layer 13. For AlGaN with a high Al composition, it is not easy to increase the hole concentration if Mg is doped, but if polarization doping is used, the hole concentration can be increased, and the hole injection efficiency into the active layer 12 can be improved. In addition, if polarization doping is used, Mg may not be doped, so the crystallinity can be improved.

[0058] If the Al composition of the composition graded layer 14 is set as described above, polarization due to crystal distortion is continuously generated in the composition graded layer 14 in the thickness direction. Holes are generated in the composition graded layer 14 in a manner that cancels the fixed charge generated by the polarization. The generated holes are distributed in the composition graded layer 14. Therefore, the holes are widely distributed in the thickness direction from the electron blocking layer 13 side in the composition graded layer 14, and the whole becomes p-type. In this p-type region, the hole concentration is 1×10 16 cm -3 ~1×10 20 cm -3 The hole concentration decreases as the distance from the electron blocking layer 13 increases. The number of holes decreases near the interface of the composition graded layer 14 with the p-type contact layer 15 because the energy band bends when the Fermi levels tend to be aligned due to the p-type heterojunction.

[0059] It is preferred that the maximum Al composition of the first composition gradient layer (the Al composition at the interface formed with the electron blocking layer 13) is 1% to 20% lower than the Al composition of the electron blocking layer 13. The polarization generated by the distortion can further increase the hole concentration. For example, the maximum Al composition is 65% to 95%.

[0060] In addition, it is preferred that the minimum value of the Al component of the first component gradient layer (the Al component at the interface formed with the second component gradient layer) is 3% to 30% lower than the maximum value of the Al component of the first component gradient layer. The polarization generated by the distortion can further increase the hole concentration. In addition, it is also preferred to have an Al component with an energy band that does not absorb the luminescent wavelength.

[0061] In addition, the reduction rate of the Al component of the first component gradient layer is preferably 0.1% / nm to 0.3% / nm. By reaching such a range, the hole concentration of the first component gradient layer can be further increased. In addition, the reduction rate of the Al component can also be constant, in other words, the reduction rate can also change linearly or not be constant.

[0062] The first composition graded layer is undoped. However, it can also be doped with Mg. It is expected that the hole concentration can be further increased by the p-type impurity. In this case, the Mg concentration is, for example, 1×10 20 cm -3 the following.

[0063] The second composition gradient layer is a layer having a higher Mg concentration than that of the first composition gradient layer, and other than that, the Al composition is set in the same manner as the first composition gradient layer. In other words, the Al composition changes in the thickness direction, and is set to decrease as the distance from the electron blocking layer 13 increases. By doping the second composition gradient layer with Mg, it can be well connected to the p-type contact layer 15.

[0064] The difference between the maximum Al component of the second component gradient layer (the Al component at the interface formed with the first component gradient layer) and the minimum Al component of the first component gradient layer is 0% to 5%, and is preferably the same as the minimum Al component of the first component gradient layer. In other words, the Al component is preferably continuous from the first component gradient layer to the second component gradient layer.

[0065] Furthermore, it is preferable that the minimum Al composition value of the second composition graded layer (Al composition at the interface with the p-type contact layer 15 ) is 3% to 30% lower than the maximum Al composition value of the second composition graded layer.

[0066] Furthermore, the reduction rate of the Al component of the second composition graded layer is in a similar range to that of the first composition graded layer. Alternatively, the reduction rate of the Al component of the second composition graded layer may be the same as that of the first composition graded layer.

[0067] The Mg concentration of the second composition graded layer may be any as long as it is higher than that of the first composition graded layer, but is preferably 3×10 20 cm -3 This is to suppress the series resistance.

[0068] In the first embodiment, the Al composition of the composition graded layer 14 decreases continuously, but it may also decrease in steps. However, it is preferable that the region where the Al composition is constant is as small as possible.

[0069] In addition, the ratio of the thickness of the first composition graded layer to the composition graded layer 14 is preferably 0.4 to 0.7. This range can sufficiently improve the hole concentration formed by polarization doping, and also improve the contact between the composition graded layer 14 and the p-type contact layer 15. More preferably, it is 0.4 to 0.6.

[0070] The composition graded layer 14 does not necessarily need to be a double-layer structure of a first composition graded layer and a second composition graded layer, but may be a first composition graded layer only. In addition, it may be a structure of three or more layers with different Al composition change rates, Mg concentrations, etc.

[0071] The thickness of the composition graded layer 14 is preferably 50% to 90% of the total thickness of the electron blocking layer 13, the composition graded layer 14, and the p-type contact layer 15. Within this range, the function as the p-type layer can be sufficiently improved.

[0072] Instead of the composition graded layer 14, a layer composed of Mg-doped p-type AlGaN may be provided. In this case, the Mg concentration is, for example, 1×10 17 cm -3~1×10 19 cm -3 In addition, the Al composition is, for example, 40% to 80%.

[0073] The p-type contact layer 15 is located on the composition graded layer 14. The p-type contact layer 15 is composed of Mg-doped p-GaN, or p-AlGaN with an Al composition lower than the minimum Al composition of the composition graded layer 14, for example, less than 50%, preferably less than 30%.

[0074] When the p-type contact layer 15 is GaN, the thickness is preferably greater than 1 nm and less than 50 nm. GaN absorbs ultraviolet light radiated from the active layer 12, but ultraviolet light can be transmitted by being sufficiently thinned. Therefore, a significant decrease in external quantum efficiency can be avoided. It is preferably greater than 1 nm and less than 10 nm. The Mg concentration of the p-type contact layer 15 is, for example, 1×10 20 cm -3 ~1×10 22 cm -3 .

[0075] Alternatively, the p-type contact layer 15 may be composed of a plurality of layers with different Al compositions and Mg concentrations. In the case of being composed of a plurality of layers, the uppermost layer in contact with the p-side electrode 17 is preferably p-GaN, or AlGaN with a low Al composition. This is to reduce the contact resistance of the p-side electrode 17. In this case, the AlGaN with a low Al composition is less than 50% of the Al composition, preferably less than 30%. In the case of making the p-type contact layer 15 AlGaN with an Al composition of less than 50%, the thickness is preferably less than 20 nm. Sufficient thinning allows ultraviolet light to pass through.

[0076] A hole 23 reaching the depth of the n-type layer 11 is provided in a local area of ​​the surface of the p-type contact layer 15. The hole 23 is a structure for exposing the n-type layer 11 and providing the n-side electrode 16.

[0077] like Figure 2 As shown, the hole 23 is in a dot shape, and a plurality of holes are provided. Moreover, the dots are arranged in a regular triangle lattice pattern. However, they are not provided near one side of the light-emitting element 1. This is for the purpose of ensuring the formation area of ​​the p-side pad electrode 22 as described later. By making the holes 23 in a dot-shaped arrangement pattern like this, the surface area of ​​the p-type contact layer 15 is left as large as possible to expand the light-emitting area, and the current diffusibility within the surface is not impaired.

[0078] The planar pattern of the hole 23 is a circle. In addition, it can also be a regular hexagon, a square, an equilateral triangle, etc. For example, it can also be a regular hexagonal pattern with the side surface being an m-plane.

[0079] In the first embodiment, the arrangement of the holes 23 is made into a regular triangle lattice pattern, but it may be made into a square lattice pattern, a honeycomb pattern, or the like.

[0080] The diameter of the hole 23 and the center-to-center distance of adjacent holes 23 are preferably within the following ranges. This can achieve an increase in the light emitting area and an improvement in the current diffusion within the surface. The diameter of the hole 23 is preferably 30 μm to 60 μm. In addition, the center-to-center distance of adjacent holes 23 is preferably 100 μm to 250 μm.

[0081] The n-side electrode 16 is disposed on and in contact with the n-type layer 11 exposed at the bottom surface of the hole 23. The material of the n-side electrode 16 is Ti / Al, V / Al, etc. Here, A / B means that A and B are stacked in order from the n-type layer 11 side. Figure 2 Thus, by forming the n-side electrode 16 into a dot-shaped planar pattern in which a plurality of dots are arranged, a reduction in the light emitting area can be suppressed and the current can be diffused in the plane.

[0082] The p-side electrode 17 is disposed on and in contact with the p-type contact layer 15, and is disposed on the entire surface except for the end. The material of the p-side electrode 17 is Ru, Rh, or an alloy with them as the main component. These materials can achieve good contact with the p-type contact layer 15. In addition, the p-side electrode 17 may be composed of a plurality of layers. In this case, the layer in contact with the p-type contact layer 15 may be Ru, Rh, or an alloy with them as the main component. For example, a structure in which a transparent electrode layer such as ITO or IZO is stacked on the Ru layer or the Rh layer may also be used.

[0083] The thickness of the p-side electrode 17 is set to allow ultraviolet light of the emission wavelength to pass through. The p-side electrode 17 is Ru, Rh, or an alloy containing them as the main component, so although the reflectivity of deep ultraviolet light is relatively high, it is still insufficient to further improve the light extraction efficiency of the light-emitting element 1. Therefore, by providing the DBR layer 19 and making the p-side electrode 17 thinner, the ultraviolet light from the active layer 12 passes through the p-side electrode 17, and the ultraviolet light can be efficiently reflected by the DBR layer 19.

[0084] The thickness of the p-side electrode 17 is preferably 1 nm to 50 nm. Within this range, good contact is achieved with the p-type contact layer 15, and ultraviolet light that has passed through the p-side electrode 17 can be efficiently reflected by the DBR layer 19. A more preferred thickness is 1 nm to 30 nm, and even more preferably 1 nm to 20 nm.

[0085] As described later, in Embodiment 1, DBR layer 19 is used on p-side electrode 17 instead of conventional Al. DBR layer 19 has a higher reflectivity of UVC than Al, and therefore can reflect more ultraviolet light that has passed through p-side electrode 17.

[0086] In the case where an Al layer is formed instead of the DBR layer 19, if the p-side electrode 17 is made thinner, the p-type contact layer 15 may be exposed in a local area, and the Al layer may contact the p-type contact layer 15 to deteriorate the contact resistance. However, in the first embodiment, the DBR layer 19 is provided instead of the Al layer, and the DBR layer 19 is an insulator. Therefore, even if the p-side electrode 17 is thin and the DBR layer 19 contacts the p-type contact layer 15, the contact resistance will not deteriorate, and good contact can be maintained.

[0087] The etching stop layer 18 is provided in a predetermined region on the n-side electrode 16 and on the p-side electrode 17. Hereinafter, the portion of the etching stop layer 18 on the n-side electrode 16 is referred to as the etching stop layer 18A, and the portion on the p-side electrode 17 is referred to as the etching stop layer 18B. The etching stop layer 18 is a layer that functions as a stopper when the holes 24 and 25 described later are formed in the DBR layer 19 and the protective layer 20.

[0088] The etching stop layer 18A is provided on the entire surface of the n-side electrode 16 except for the vicinity of the end portion. Therefore, the etching stop layer 18A has the same pattern as that of the n-side electrode 16.

[0089] The etching stop layer 18B is in a dot shape. It may also be a combination of a dot shape and a stretched shape (wiring shape). The etching stop layer 18B should be provided at the position of the hole 25 described later. In addition, it is set so that the hole 25 becomes the inside of the etching stop layer 18B when viewed from above.

[0090] As described above, the etching stop layer 18B is limited to a local area on the p-side electrode 17. The reason is as follows. The entire surface of the etching stop layer 18B is formed on the p-side electrode 17, and most of the ultraviolet light that has passed through the p-side electrode 17 is incident on the etching stop layer 18, and a part of the ultraviolet light is absorbed by the etching stop layer 18B. Therefore, even if the DBR layer 19 is provided, the reflectivity is not sufficiently improved. Therefore, the etching stop layer 18B is limited to the area where the hole 25 is provided, and the absorption of ultraviolet light by the etching stop layer 18B is suppressed.

[0091] The material of the etching stop layer 18 is a conductive material that is resistant to dry etching of the DBR layer 19 and the protective layer 20. For example, it is a conductive material that is resistant to dry etching using fluorine gas. Specifically, it is Ti, TiN, Ni, Pt, Al, etc. In addition, it can also be a multilayer film containing these materials.

[0092] When the etching stop layer 18B is a multilayer film, the first layer in contact with the p-side electrode 17 is preferably an Al layer or a metal layer with Al as the main component. The ultraviolet light that passes through the p-side electrode 17 and enters the etching stop layer 18B can be reflected, and the light extraction efficiency can be further improved. In addition, in this case, the thickness of the Al layer is preferably 10nm to 500nm, and more preferably 80nm to 200nm. In the case of a multilayer film, for example, Al / Ti / Ni / Ti / Al and Al / Ti / Pt / Ti / Al can be used.

[0093] Compared to the area of ​​the p-side electrode 17, the overall area of ​​the etching stop layer 18B is preferably less than 60% thereof. This is to make the area of ​​the etching stop layer 18B that absorbs ultraviolet light of the emission wavelength as small as possible, to make the contact area between the p-side electrode 17 and the DBR layer 19 as large as possible, and to further improve the light extraction efficiency. It is more preferably less than 50%, and further preferably less than 25%. In addition, the overall area of ​​the etching stop layer 18B is preferably more than 3% of the area of ​​the p-side electrode 17. This means that it is set to be greater than the area in the case where the etching stop layer is configured only directly below the hole 25 that connects the p-side electrode 17 to the p-side pad electrode 22.

[0094] The diameter of the point of the etching stop layer 18B is set according to the diameter of the hole 25. The diameter of the point of the etching stop layer 18B is preferably 1.2 times or more of the diameter of the hole 25. If it is 1.2 times or more, even if the position of the hole 25 is deviated or the diameter error occurs, the hole 25 can be located inside the outer circle of the etching stop layer 18B when viewed from above, and the function of the etching stop layer 18B can be maintained. In addition, the diameter of the point of the etching stop layer 18B is preferably 1.5 times or less of the diameter of the hole 25. If it is less than 1.5 times, the absorption of ultraviolet light by the etching stop layer 18B can be sufficiently reduced. In addition, the distance between the points of the etching stop layer 18B is preferably 1 to 6 times the diameter of the hole 25.

[0095] The DBR layer 19 is provided to cover the p-side electrode 17, the etching stop layer 18, the hole 23, and the side surface of the semiconductor layer (the stacked structure from the n-type layer 11 to the p-type contact layer 15) exposed on the peripheral side surface of the element. Hereinafter, the area on the p-side electrode 17 other than the area where the etching stop layer 18B is provided is contacted by the DBR layer 19. The DBR layer 19 is a layer provided to reflect the ultraviolet light that passes through the p-side electrode 17. In addition, the DBR layer 19 is also a layer that reflects the ultraviolet light toward the peripheral part of the element and the hole 23.

[0096] When an Al layer is provided instead of the DBR layer 19, the Al layer is a conductor and therefore cannot cover the side surfaces of the semiconductor layer (the side surfaces of the device periphery and the side surfaces of the hole 23). However, the DBR layer 19 is an insulator and therefore can also cover the side surfaces of the device periphery and the side surfaces and bottom surface of the hole 23. Therefore, compared with the case where the Al layer is used, the area for reflecting ultraviolet light becomes larger, and the light extraction efficiency can be improved.

[0097] The DBR layer 19 is a structure obtained by alternately and repeatedly stacking a low refractive index layer and a high refractive index layer having a higher refractive index than the low refractive index layer, and the thickness of each layer is set in such a way that the reflectivity of the ultraviolet light of the emission wavelength becomes high. Each layer can be an insulating material that transmits the ultraviolet light of the emission wavelength, and the high refractive index layer can use HfO2, ZrO2, etc., and the low refractive index layer can use SiO2, Al2O3, MgF2, etc. In particular, HfO2 has high durability with respect to deep ultraviolet light and is suitable as a material for the DBR layer 19.

[0098] In Embodiment 1, the area of ​​the etching stop layer 18 on the p-side electrode 17 is small, so the contact area between the p-side electrode 17 and the DBR layer 19 becomes large. Therefore, most of the ultraviolet light radiated from the active layer 12 to the p-side electrode 17 side and transmitted through the p-side electrode 17 is incident on the DBR layer 19, and the ultraviolet light can be reflected toward the substrate 10 side by the DBR layer 19. In other words, the reduction in light extraction efficiency caused by the provision of the etching stop layer 18 can be suppressed.

[0099] The material, thickness, and number of layers of the DBR layer 19 are preferably set so that the reflectivity of the DBR layer 19 is 95% or more. Here, the reflectivity is the reflectivity when ultraviolet light of the emission wavelength is incident perpendicularly to the main surface of the DBR layer 19. A reflectivity of 97% or more is more preferred, and a reflectivity of 99% or more is further preferred.

[0100] The DBR layer 19 preferably has a reflectivity dependency of 90% or more at any incident angle in the range of -60° to 60°. The reflectivity dependency of the DBR layer 19 can be set by the refractive index, thickness, and number of layers of each layer of the DBR layer 19.

[0101] The protective layer 20 is provided to cover the DBR layer 19. The material of the protective layer 20 is SiO2 or the like. A plurality of holes 24 and 25 penetrating the protective layer 20 and the DBR layer 19 are provided in predetermined regions of the protective layer 20 and the DBR layer 19. The hole 24 is a hole for connecting the etching stop layer 18A to the n-side pad electrode 21. The hole 25 is a hole for connecting the etching stop layer 18B to the p-side pad electrode 22.

[0102] The hole 24 is provided in the region corresponding to the upper portion of the etching stop layer 18A. Therefore, the arrangement pattern of the hole 24 is the same as that of the etching stop layer 18A. In addition, the hole 24 is provided so as to be located inside the outer circumference of the etching stop layer 18A when viewed from above. For example, the diameter of the hole 24 is 0.5 to 0.9 times the diameter of the etching stop layer 18A. The plane pattern of the hole 24 is a circle, the same as the etching stop layer 18A. In addition, it may be a regular hexagon, a square, a regular triangle, etc.

[0103] The hole 25 is provided in a region corresponding to the upper portion of the etching stop layer 18B. The hole 25 is dot-shaped, and the plane pattern is a circle. Figure 2 As shown, a plurality of holes 25 are arranged along one side of the light emitting element 1 near the side where the holes 23 are not provided. The holes 25 are provided inside the outer circumference of the etching stop layer 18B in a plan view.

[0104] The diameter of the hole 25 is preferably 60 μm or less. By reducing the diameter of the hole 25, the diameter of the etching stop layer 18B can also be reduced, so that the light extraction efficiency can be improved. It is more preferably 50 μm or less, and further preferably 40 μm or less. In addition, the diameter of the hole 25 is preferably 10 μm or more. This is to achieve good conduction between the p-side electrode 17 and the p-side pad electrode 22. It is more preferably 20 μm or more.

[0105] The center-to-center distance of adjacent holes 25 is preferably 50 μm to 250 μm. Within this range, both the current diffusibility and the light extraction efficiency can be adequately improved. In addition, each point of the etching stop layer 18B is provided corresponding to the hole 25, so the center-to-center distance between adjacent points for each point of the etching stop layer 18B is also preferably within the same range as the center-to-center distance of the adjacent holes 25.

[0106] The planar pattern of the holes 25 does not need to be a circle, and may be a regular triangle, a square, a regular hexagon, or the like.

[0107] In addition, the number of holes 25 and etching stop layer 18B can be one or more. However, in order to diffuse the current in the plane, it is preferred to make holes 25 and etching stop layer 18B points and provide multiple points as in Embodiment 1. In addition, when multiple points are provided, they can be arranged in a straight line as in Embodiment 1, but can also be arranged in two dimensions. For example, they can also be arranged in a regular triangle lattice, a square lattice, a honeycomb, etc. In addition, in order to improve the diffusion of the current in the plane, the point shape and the stretch shape can also be combined. For example, it can also be a pattern in which wiring extending in the opposite side direction is connected to the arranged points.

[0108] Alternatively, a reflective layer composed of Al, Mg or an alloy mainly composed of Al, Mg or Mg may be provided between the DBR layer 19 and the protective layer 20 in contact with the DBR layer 19. However, no reflective layer is provided in the formation area of ​​the holes 24 and 25. The reflectivity of the DBR layer 19 is incident angle dependent, so there is a situation where ultraviolet light incident at a larger angle relative to the DBR layer 19 cannot be fully reflected. For example, when the number of stacking layers of the DBR layer 19 is reduced, the incident angle dependence becomes significant. On the other hand, since the reflective layer is metal, the incident angle dependence is small. Therefore, by providing the reflective layer in contact with the DBR layer 19, ultraviolet light with a large incident angle can also be reflected, and the angular dependence of the reflectivity of the DBR layer 19 can be supplemented. The thickness of the reflective layer is, for example, 30nm to 200nm. If it is within this range, the reflectivity can be fully improved.

[0109] The n-side pad electrode 21 is provided on the protective layer 20 and in a region corresponding to the upper portion of each hole 24. The etching stop layer 18A is connected to the n-side pad electrode 21 through each hole 24. Thus, the n-side pad electrode 21 and the n-side electrode 16 are electrically connected.

[0110] The p-side pad electrode 22 is provided on the protective layer 20 and in a region corresponding to the upper portion of each hole 25. Furthermore, the etching stop layer 18B is connected to the p-side pad electrode 22 via each hole 25. Thus, the p-side pad electrode 22 is electrically connected to the p-side electrode 17. In this way, the p-side pad electrode 22 and the p-side electrode 17 are connected in a point shape via the hole 25, so that a larger contact area between the p-side electrode 17 and the DBR layer 19 can be obtained, and a larger area for reflecting ultraviolet light can be obtained.

[0111] As described above, in the light emitting element 1 of the first embodiment, the etching stop layer 18B is provided in a dot shape, and the area where the p-side electrode 17 contacts the DBR layer 19 becomes larger. Therefore, the ultraviolet light that passes through the p-side electrode 17 can be efficiently reflected by the DBR layer 19. As a result, the light extraction efficiency of the light emitting element 1 can be improved.

[0112] 2. Method for manufacturing light-emitting element

[0113] Next, a method for manufacturing the light emitting element 1 according to Embodiment 1 will be described with reference to the drawings.

[0114] First, an n-type layer 11, an active layer 12, an electron blocking layer 13, a composition gradient layer 14, and a p-type contact layer 15 are sequentially stacked on a substrate 10 through a buffer layer by MOCVD (see Figure 3 ).

[0115] Next, a predetermined region of the p-type contact layer 15 is dry-etched until it reaches the n-type layer 11 to form a hole 23 (see Figure 4).

[0116] Next, a p-side electrode 17 is formed on the p-type contact layer 15 by sputtering or evaporation (see Figure 5 ).

[0117] Next, the n-side electrode 16 is formed on the n-type layer 11 exposed at the bottom of the hole 23 by sputtering or evaporation. Then, a heat treatment is performed to reduce the contact resistance of the n-side electrode 16 and activate the p-type impurities. Next, etching stop layers 18A and 18B are formed on predetermined regions on the n-side electrode 16 and on the p-side electrode 17 (see FIG. 1 ). Figure 6 ).

[0118] Next, the DBR layer 19 is formed so as to cover the p-side electrode 17, the etching stop layers 18A and 18B, the hole 23, and the outer peripheral side surface of the element (see Figure 7 ) The DBR layer 19 is formed by a method such as sputtering, vapor deposition, or ALD.

[0119] Next, the protective layer 20 is formed by CVD, sputtering, vapor deposition, etc. so as to cover the DBR layer 19 (see Figure 8 ).

[0120] Next, holes 24 and 25 penetrating the protective layer 20 and the DBR layer 19 are formed by dry etching. Here, since the etching stop layers 18A and 18B are formed, the formation of the holes 24 and 25 is stopped at the stage where the etching stop layers 18A and 18B are exposed. Therefore, the holes 24 and 25 can be formed with high precision.

[0121] Next, an n-side pad electrode 21 and a p-side pad electrode 22 are formed in a predetermined region on the protective layer 20. Thus, the etching stop layer 18 on the n-side electrode 16 is connected to the n-side pad electrode 21 via the hole 24, and the etching stop layer 18 on the p-side electrode 17 is connected to the p-side pad electrode 22 via the hole 25. Figure 1 Light-emitting element 1 according to Embodiment 1 is shown.

[0122] 3. Various Experimental Examples of Implementation Method 1

[0123] A DBR set to have a high reflectivity with respect to deep ultraviolet light was produced, and the wavelength dependence of the reflectivity of the DBR was measured. In addition, the wavelength dependence of the reflectivity was also measured for the case where Al was formed on the DBR in contact with the DBR. In addition, the wavelength dependence of the reflectivity of Al was also measured for comparison. Fig.10This is a graph showing the wavelength dependence of the reflectivity of DBR, DBR / Al, and Al. The DBR is a structure in which HfO2 and SiO2 are alternately stacked, and is paired with a film thickness simulated so that the reflectivity becomes 97% or more at a wavelength of 270nm to 280nm. In addition, the thickness of the Al layer is 1000nm. In addition, light is incident on the main surface of the DBR and Al at an incident angle of 10° and the reflectivity is measured.

[0124] like Fig.10 In this way, it can be known that in the UVC band below the wavelength of 280nm, the reflectivity of DBR and DBR / Al can be made higher than the reflectivity of Al. In addition, it can be known that if DBR / Al is adopted, the reflectivity can be further improved compared with the DBR alone. At a wavelength of 280nm, the reflectivity of Al is 91.3%, while the reflectivity of DBR is 98.1%, and the reflectivity of DBR / Al is approximately 99.3%. From the results, it can be seen that by adopting the structure of Ru / DBR or Rh / DBR, the reflectivity can be improved compared with the structure of Ru / Al or Rh / Al.

[0125] 4. Various variations of implementation mode 1

[0126] It can also be constructed such that an intermediate electrode with a wiring pattern is provided between the n-side pad electrode 21 and the etching stop layer 18A and between the p-side pad electrode 22 and the etching stop layer 18B via an insulating film, and each etching stop layer 18A is connected to the n-side pad electrode 21, and each etching stop layer 18B is connected to the p-side pad electrode through the intermediate electrode.

[0127] In the first embodiment, in order to ensure the formation area of ​​the p-side pad electrode 22, the points of the n-side electrode 16 cannot be arranged on the entire surface, but by providing the intermediate electrode, the arrangement of the points of the n-side electrode 16 can be freely determined, so the points of the n-side electrode 16 can be arranged on the entire surface. As a result, the in-plane uniformity of light emission can be improved, and the light emission area can be expanded. In addition, by providing the intermediate electrode, the plane pattern of the n-side pad electrode 21 and the p-side pad electrode 22 can be freely set.

Claims

1. A light-emitting element, which is a flip-chip type and ultraviolet light-emitting element, characterized in that: have: An n-type layer composed of an n-type Group III nitride semiconductor; an active layer disposed on the n-type layer and composed of a Group III nitride semiconductor; A p-type layer, which is disposed on the active layer and is composed of a p-type Group III nitride semiconductor; A p-side electrode disposed on the p-type layer and including a layer composed of Ru, Rh or an alloy containing them as main components and in contact with the p-type layer, and having a thickness set to allow ultraviolet light of the emission wavelength to pass therethrough; an insulating DBR layer, which is in contact with and disposed on a portion of the p-side electrode and reflects ultraviolet light of a light-emitting wavelength; as well as A second p-side electrode is electrically connected to the p-side electrode via a hole formed in a region of the DBR layer above the p-side electrode.

2. The light emitting element according to claim 1, characterized in that The DBR layer is provided in contact with and on a portion of the p-side electrode, and is provided in contact with a side surface of at least one of the n-type layer, the active layer, and the p-type layer.

3. The light emitting element according to claim 1 or 2, characterized in that: The light emission wavelength is greater than or equal to 200 nm and less than or equal to 280 nm.

4. The light emitting element according to claim 1 or 2, characterized in that: The DBR layer includes HfO2.

5. The light emitting element according to claim 1 or 2, characterized in that: The p-side electrode has a thickness of not less than 1 nm and not more than 50 nm.

6. The light emitting element according to claim 1 or 2, characterized in that: The p-type layer has a p-type contact layer that is in contact with the p-side electrode and is made of GaN. The p-type contact layer has a thickness of not less than 1 nm and not more than 50 nm.

7. The light emitting element according to claim 1 or 2, characterized in that: The p-type layer has a p-type contact layer that is in contact with the p-side electrode and is composed of AlGaN having an Al composition of 50% or less. The thickness of the p-type contact layer is less than 20 nm.

8. A method for manufacturing a light-emitting element, which is a method for manufacturing a flip-chip ultraviolet light-emitting element, characterized in that: have: an n-type layer forming step of forming an n-type layer composed of an n-type Group III nitride semiconductor; an active layer forming step of forming an active layer composed of a Group III nitride semiconductor on the n-type layer; a p-type layer forming step of forming a p-type layer composed of a p-type Group III nitride semiconductor on the active layer; a p-side electrode forming step, in which a p-side electrode including a layer composed of Ru, Rh or an alloy mainly composed of these and in contact with the p-type layer and having a thickness that allows ultraviolet light of a light emission wavelength to pass therethrough is formed on the p-type layer; a DBR layer forming step of forming an insulating DBR layer that reflects ultraviolet light of a light emission wavelength on a portion of the p-side electrode in contact with the portion of the p-side electrode; as well as and a second p-side electrode forming step of forming a second p-side electrode so as to be electrically connected to the p-side electrode via a hole formed in a region of the DBR layer above the p-side electrode.

Citation Information

Patent Citations

  • Light-emitting element and illumination device including the same

    JP2015220456A

  • Semiconductor light-emitting element and manufacturing method thereof

    JP2022030948A

  • Light emitting device

    JP2023034227A